From Weber to Kafka: Political Instability and the Overproduction of Laws - Gratton, Gabriele; Guiso, Luigi; Michelacci, Claudio; Morelli, Massimo (American Economic Review, 2021)
With inefficient bureaucratic institutions, the effects of laws are hard to assess and incompetent politicians may pass laws to build a reputation as skillful reformers. Since too many laws curtail bureaucratic efficiency, this mechanism can generate a steady state with Kafkaesque bureaucracy. Temporary surges in political instability heighten the incentives to overproduce laws and can shift the economy towards the Kafkaesque state. Consistent with the theory, after a surge in political instability in the early 1990s, Italy experienced a significant increase in the amount of poor-quality legislation and a decrease in bureaucratic efficiency. (JEL D72, D73)